African history a very short introduction - Parker, John 1960-; Rathbone, Richard 1942- (Very short introductions, 2007)
Essential reading for anyone interested in the African continent and the diversity of human history, this introduction looks at Africa's past and reflects on the changing ways it has been imagined and represented. Key themes in current thinking about Africa's history are illustrated with a range of historical examples